2023
DOI: 10.1002/acm2.14009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial devices for patient specific QA of stereotactic radiotherapy plans

Abstract: Stereotactic radiotherapy (SRT) methods have become common for the treatment of small tumors in various parts of the body. Small field dosimetry has a unique set of challenges when it comes to the pre‐treatment validation of a radiotherapy plan that involves film dosimetry or high‐resolution detectors. Comparison of commercial quality assurance (QA) devices to the film dosimetry method for pre‐treatment evaluation of stereotactic radiosurgery (SRS), fractionated SRT, and stereotactic body radiation therapy tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This result is consistent with a similar recent study comparing various detector arrays against film dosimetry. 24 The Fourier analysis in the present work (see Figure 3 ) shows that the detector spacing in the SRS MapCHECK is sufficient for the investigated SRS fields. This highlights the importance of a small distance to agreement (DTA) value for high‐resolution detector arrays when altering the dose difference (DD) to detect errors.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This result is consistent with a similar recent study comparing various detector arrays against film dosimetry. 24 The Fourier analysis in the present work (see Figure 3 ) shows that the detector spacing in the SRS MapCHECK is sufficient for the investigated SRS fields. This highlights the importance of a small distance to agreement (DTA) value for high‐resolution detector arrays when altering the dose difference (DD) to detect errors.…”
Section: Discussionmentioning
confidence: 53%
“…Data from another study on SRS deliveries on target volumes of sizes 0.43–161.13cmm is also included to depict the trend. 24 This trend is indicative of the complexity behind the influencing factors, which may include treatment plan and delivery as well as measuring technique. Figure 8 , however, helps underline the role of the Nyquist theory on MLC error detectability, whereby an optimal detector spacing should preferably lie within the boundaries defined by the vertical dotted lines.…”
Section: Discussionmentioning
confidence: 99%
“…For both the gamma criteria used. James S et al, [ 19 ] also observed better gamma agreement with EBT XD film compared EPID. They reported average gamma agreement of 96.7% and 95.9% for EBT XD and EPID respectively.…”
Section: Discussionmentioning
confidence: 96%
“…James et al. 24 compared commercial quality assurance (QA) devices (EBT‐XD film, IBA Matrixx Resolution, SNC ArcCHECK, Varian aS1200 EPID, SNC SRS MapCHECK, and IBA myQA SRS) to film dosimetry for pre‐treatment evaluation of stereotactic radiosurgery (SRS), fractionated SRT, and stereotactic body radiation therapy treatment plans. Their work compared gamma pass rates for a set of forty plans as well as two plans containing MLC positioning error scenarios.…”
Section: Discussionmentioning
confidence: 99%